The role of aromatic rings, heterocyclic rings, and hydroxyl groups in increasing hydrogen production using activated carbon-based photocatalysts - Fitria Indra Septi; Willy Satrio Nugroho; Purnami; Dionysius Joseph Djoko Herry Santjojo; I Nyoman Gede Wardana (Universitas Muhammadiyah Magelang, 2026)
Hydrogen production using photocatalysis with activated carbon (AC) combined with curcumin and CTP has been investigated. Curcumin contains two aromatic rings and two ”“OH groups, while CTP contains two aromatic rings, one pyran heterocyclic ring, and six ”“OH groups at specific positions. However, the combined performance of these materials with AC has not been fully optimized, highlighting the need for further research to understand their chemical interactions in photocatalytic processes and their potential for renewable energy applications. This study aimed to determine the role of pyran heterocyclic rings and ”“OH groups in hydrogen production. The results showed that hydrogen production using pure AC was 115.75 Î¼mol/g, while AC + curcumin and AC + CTP produced 1297.8 Î¼mol/g and 1462.6 Î¼mol/g, respectively. The higher hydrogen production in AC + CTP compared to AC + curcumin is attributed to the presence of pyran heterocyclic rings, which enhance photocatalyst stability and efficiency by reducing electron”“hole recombination and expanding the light absorption spectrum, thereby increasing hydrogen evolution. Although the stacking interactions and active sites in the form of ”“OH, C”“H, and C”“O groups in AC + CTP are fewer than in AC + curcumin, the presence of oxygen atoms in the pyran heterocyclic ring contributes to greater hydrogen production. This study contributes to the selection of effective photocatalyst materials based on compound composition to support clean and sustainable hydrogen energy as an alternative to fossil fuels.